Med Aromat Plants 2019
DOI: 10.35248/2167-0412.19.8.337
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Flavonoid Contents of Some Plant Extracts from Tunisia Southern Landscape by Using Different Extraction Techniques: The Case of Retama reatam

Abstract: Nowadays traditional medicine, a source of several bioactive molecules for therapeutic purposes, has become a cure for various diseases. In fact, the evaluation of plant exploitation has become progressively significant and this for their therapeutic effects of many traditional medicines may be due to the immense presence of natural antioxidants. In this respect, Retama reatam was chosen among six herbal Tunisian plants traditionally known for their therapeutic virtues, as the best source of total polyphenol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…3 c) confirms with a compromise of 99% that setting parameters at their maximum level leads to obtaining a maximum flavonoid content equal to 45 mg QE/g DE. This TFC value remains relatively high with respect to previously reported result obtained from R. sphaerocarpa by maceration [ 43 ], and largely high compared to that recorded through maceration of R. raetam [ 42 ]. According to a similar study, choosing the appropriate ratio of ethanol to water efficiently improved the extraction of valuable compounds like flavonoids [ 49 ].…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…3 c) confirms with a compromise of 99% that setting parameters at their maximum level leads to obtaining a maximum flavonoid content equal to 45 mg QE/g DE. This TFC value remains relatively high with respect to previously reported result obtained from R. sphaerocarpa by maceration [ 43 ], and largely high compared to that recorded through maceration of R. raetam [ 42 ]. According to a similar study, choosing the appropriate ratio of ethanol to water efficiently improved the extraction of valuable compounds like flavonoids [ 49 ].…”
Section: Resultssupporting
confidence: 46%
“…Our optimized yield was higher than that of conventional extraction methods for other retama genus. For the species Retama raetam , Rejab et al [ 42 ] have found 15.36% and 2.55% as extraction yield obtained by maceration with ethanol and hexane, respectively. Moreover, it was reported that maceration with methanol 70% gave a yield of 23.26% and 18.13% from the stems and seeds of Retama monosperma , respectively [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Maulina et al also reported that temperature and drying methods resulted in different values of total phenolic content (24). The differences in maceration methods can also affect the value of total phenolic content (25).…”
Section: Discussionmentioning
confidence: 99%
“…The total flavonoid content (TFC) was determined using the aluminum chloride (AlCl3) colorimetric technique following Rejab and Ksibi (2019) with a few minor changes. About 300 L of 10% w/v sodium carbonate (NaCO3) (Sigma-Aldrich, USA) was added to an aliquot of 100 L of extract with concentrations of 20-200 g/mL in 1 mL of distilled water.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%